Analyses of bioindicators and physicochemical parameters of water of Lake Tondano, North Sulawesi Province, Indonesia - PRABANG SETYONO; WIDHI HIMAWAN (Society for Indonesian Biodiversity, 2018)
. Setyono P, Himawan W. 2018. Analyses of bioindicators and physicochemical parameters of water of Lake Tondano, North Sulawesi Province, Indonesia. Biodiversitas 19: 867-874. The water quality of Lake Tondano is affected by various anthropogenic activities on the water body and catchment area. The purposes of this research were (i) to identify a pollution load based on the study of bioindicators and physicochemical parameters and (ii) to identify the trophic level of the Lake Tondano. The research data were collected by direct water sampling and analyses of a secondary data. The plankton identification was conducted in a laboratory. The data were analyzed to determine biodiversity index (ID) using the Shannon Weiner formula. A comparison between physicochemical parameters and the standard in the government regulation number 82, the year of 2001 and the value of diversity index were used to determine the pollution level. The trophic level was calculated with the Carlson Formula. The results showed that the diversity index (H') in Lake Tondano was 1.904 (phytoplankton), 1.712 (zooplankton) and 2.086 (benthos) which indicated a low to mid-level pollution. Based on the government regulation, the Eris station had inappropriate water quality for the present utilization (Class II). The trophic state was categorized as eutrophic towards hypertrophic condition indicated by domination of the phytoplankton and large covers of the water hyacinth.